Analisis Peran Transparansi Audit dalam Upaya Membangun Kepercayaan Nasabah Bank Syariah - Anggella, Pinkan Ajeng; Salsabila, Resa; Utama, Fikri Rizki (Teewan Journal Solutions, 2026)
This study aims to analyze the role of audit transparency in building and maintaining customer trust in Islamic banks. Using a descriptive qualitative approach, data were gathered through literature reviews and in-depth interviews with seven informants, including bank customers, Islamic bank employees, and an academic. The results indicate that audit transparency, backed by rigorous supervision from the Sharia Supervisory Board (SSB), plays a crucial role in fostering security and customer loyalty by mitigating concerns over fraud and fund mismanagement. However, the effectiveness of this transparency is still hindered by technical constraints, such as overly formal and complex financial reporting language, coupled with low public audit literacy. To overcome these barriers, Islamic banks need to reform their communication strategies by designing concise infographics and conducting proactive socialization to minimize information asymmetry. This study underscores that adaptive information disclosure serves as a key pillar in sustaining the credibility and reputation of Islamic banking in Indonesia.